Staggered Dual Kidney Transplantation. (September 2021) - Ismail, Omar Mobeen; Saedon, Mahmud; Sharma, Videha; Asderakis, Argiris; Augustine, Titus
We describe a case where a patient received a successful dual kidney transplantation in a staggered fashion. Two kidneys from a deceased donor were accepted for 2 separate primary intended recipients, however, due to unforeseen circumstances, both kidneys were eventually transplanted in a staggered fashion into an alternate single recipient. The intention behind this method was to enhance the patient's renal function and to prevent the wastage of a kidney. Despite the significantly prolonged cold ischemia times, the recipient has excellent dual graft function after 3 years. The positive outcome underpins the effectiveness of donor kidneys even with prolonged cold ischemia times outside established best practice guidelines. It also reinforces the effectiveness of dual kidney transplantation. Transplant professionals encounter complex situations occasionally where an established evidence-base or aids to decision-making are limited. This case reflects challenges in decision-making, patient counselling and consent, especially when the opportunity for the staggered dual kidney transplantation, with potential increased morbidity, came about as another recipient declined a usable kidney. It also highlights the widely differing risk appetites of different patients. Crucially, it optimised the donation process and procurement of 2 kidneys while preventing wastage. To our knowledge, this is the first report of a staggered dual kidney transplantation in a single recipient.